Comparative Study of Stone Pulverization and Clearance Rate between Patients Treated by ESWL Under Spinal Anesthesia in Comparison with ESWL Under Sedation and Analgesia - Hossain, MA (Journal of Bangladesh College of Physicians and Surgeons, 2011)
This interventional (quasi) comparative clinical study was conducted on patients with renal stone to find out the stone pulverization and clearance rate in patients treated by ESWL under spinal anesthesia and treated by ESWL under sedation and analgesia. Selected patients were grouped as 'Group-A' for ESWL under spinal anesthesia & ‘Group-B’ for ESWL under sedation & analgesia. Immediate stone clearance was much higher in Group-A (96.7%) than that of Group-B (66.7%). Although both groups demonstrated 100% clearance after 3rd follow up. In this study different numbers of shock waves were given for stone pulverization as some stones were soft, hard or very hard. Under sedation and analgesia patients could not tolerate more shock waves and stayed long time on table in targeted position due to pain. But under spinal anesthesia more shock waves application was possible. This study outcome suggest that ESWL under spinal anesthesia is a better option than ESWL under sedation and analgesia. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7950 (J Bangladesh Coll Phys Surg 2011; 29: 67-71)